2016
DOI: 10.1016/j.foodcont.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a two-peptide plantaricin produced by Lactobacillus plantarum MBSa4 isolated from Brazilian salami

Abstract: a b s t r a c tThe aim of this study was to explore the biochemical and genetic features of the two-peptide bacteriocin produced by a Lactobacillus plantarum strain isolated from Italian type salami produced in Brazil (Lb. plantarum MBSa4). Identification of bacteriocinogenic Lb. plantarum MBSa4 was performed by 16S rRNA sequencing. Expressed bacteriocin was evaluated for spectrum of activity, heat and pH stability, mechanism of action, and molecular mass. Partial purification was achieved by cation-exchange, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 69 publications
2
39
0
1
Order By: Relevance
“…Characterization of dominant Lb. plantarum from fermented sausages is revealed in many strains proposed as potential functional starter cultures with desirable technological and safety properties [ 23 , 37 , 89 , 90 ]. One of the most studied properties of indigenous Lb.…”
Section: Lb Plantarum In Traditional Food Systmentioning
confidence: 99%
“…Characterization of dominant Lb. plantarum from fermented sausages is revealed in many strains proposed as potential functional starter cultures with desirable technological and safety properties [ 23 , 37 , 89 , 90 ]. One of the most studied properties of indigenous Lb.…”
Section: Lb Plantarum In Traditional Food Systmentioning
confidence: 99%
“…Moreover, LAB, used in the manufacturing of these products, synthesize many metabolites (lactic acid, γ-aminobutyric acid, bacteriocin, reuterin and reutericycline, conjugated linoleic acid, exopolysaccharides), which have beneficial effect on human health. The LAB metabolites and the biologically active components of milk have a number of activities such as: immunomodulatory activity [4][5][6][7][8], antihypertensive [9][10][11][12][13], antitumor or anticancer activity [14][15][16][17][18], antioxidant activity [5,12,14,17,[19][20][21], antimicrobial activity [22][23][24], mineral-binding activity [25][26][27], opioid [28] etc.…”
mentioning
confidence: 99%
“…The activity of the bacteriocin produced by L . plantarum MBSa4 was not affected by temperature (4°C to 100°C, remaining active even after treatment at 121°C for 15 min) . This bacteriocin was called MBSa4, and presented antifungal activities against Penicillium roqueforti , Penicillium expansum , Fusarium sp., Mucor plumbeus , Cladosporium sp., and Debaromyces hansenii .…”
Section: Production Of Antimicrobial Compounds By Lalmentioning
confidence: 99%
“…MBSa4 was not affected by temperature (4 C to 100 C, remaining active even after treatment at 121 C for 15 min). 95 This bacteriocin was called MBSa4, and presented antifungal activities against Penicillium roqueforti, Penicillium expansum, Fusarium sp., Mucor plumbeus, Cladosporium sp., and Debaromyces hansenii. Gomaa et al 96 showed that the antifungal bacteriocin produced by L. brevis and L. paracasei isolated from dairy products inhibited the growth of Aspergillus spp.…”
Section: Production Of Antimicrobial Compounds By Lalmentioning
confidence: 99%